Focal blast crisis in concomitant myelodysplastic syndrome and chronic myelogenous leukemia - Reap, Leo (Leuk Res Rep, 2020)
Leukemic transformation of myelodysplastic syndrome (MDS) or chronic myelogenous leukemia (CML) is a well-established phenomenon. However, co-occurrence of MDS and CML is a rare phenomenon, with few reports to date. Though blast crisis typically occurs systemically with MDS or CML, rare reports of focal transformation with myeloid sarcoma (MS) have been described. We present the first known case of concomitant MDS and CML on imatinib that developed focal blastic transformation, where the leukemic clone was BCR-ABL1 positive. Local irradiation and second-generation TKI was enough to attain long-term remission. Herein, we discuss MS and its implications in both CML and MDS.